Humins in the environment: early stage insights on ecotoxicological aspects. (28th December 2018) - Muralidhara, Anitha; Bado‐Nilles, Anne; Marlair, Guy; Engelen, Victor; Len, Christophe; Pandard, Pascal
Abstract: With a growing interest in the concept of a circular economy, the use of lignocellulosic residues, such as lignins and humins, as potential renewable feedstock for biorefining processes looks increasingly promising. Many challenges remain for the sustainable use of humins, starting from the need to provide reference data reflecting actual usable feedstocks of such materials. This paper offers the first study, from this perspective, of the potential environmental fate of those materials and components, all related to furanics, a family of compounds the toxicity of which is still a matter of debate. Conventional ecotoxicity and biodegradability tests required by European regulation on the Registration, Evaluation, Authorisation and Restriction of Chemicals (REACH) for the primary evaluation of environmental hazards were conducted in combination with fish immunomarker tests to study possible long‐term effects on aquatic ecosystems. These first results are promising as humins did not give rise to any immediate ecotoxicological concerns, and hence their use could be considered in environment‐friendly applications. © 2018 Society of Chemical Industry and John Wiley & Sons, Ltd